PENGEMBANGAN APLIKASI ANDROID BERBASIS BUDAYA KOTA TANGERANG PADA PELAJARAN IPS DI KELAS IV SDN PABUARAN 1 TANGERANG - Astri Astri; Ana Nurhasanah; Ikman Nur Rahman (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to develop an android application based on the culture of Tangerang and to determine the feasibility of the application. This study utilized the R&D research method on the Brog and Gall development design modified by Sugiyono following six stages: 1) Problem analysis; 2) Data collection; 3) Product design; 4) Expert validation; 5) Design revision, and 6) Product trial. This was conducted in class IVB SDN Pabuaran 1 Tangerang. The feasibility of the product was examined by several experts such as education experts, material experts, and media experts. The validation result from media experts obtained an average score of 92% with the